2008
DOI: 10.1148/radiol.2482071478
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Myocardial Perfusion Defects, Regional Wall Motion, and Left Ventricular Function by Using 64-Section Multidetector CT

Abstract: Purpose:To evaluate the accuracy of 64-section multidetector computed tomography (CT) for the assessment of perfusion defects (PDs), regional wall motion (RWM), and global left ventricular (LV) function. Materials and Methods:All myocardial infarction (MI) patients signed informed consent. The IRB approved the study and it was HIPAAcompliant. Cardiac multidetector CT was performed in 102 patients (34 with recent acute MI and 68 without). Multidetector CT images were analyzed for myocardial PD, RWM abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
103
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 31 publications
2
103
0
2
Order By: Relevance
“…Preliminary studies have demonstrated that left and right ventricular volumes measured by CT correlate well with other established modalities (7). However, at the present time, given the limited temporal resolution of cardiac CT and the associated radiation exposure, cardiac CT cannot be recommended as a preferred method for measuring ventricular volumes and ejection fraction if alternative modalities are readily available.…”
Section: Ventricular Functionmentioning
confidence: 95%
“…Preliminary studies have demonstrated that left and right ventricular volumes measured by CT correlate well with other established modalities (7). However, at the present time, given the limited temporal resolution of cardiac CT and the associated radiation exposure, cardiac CT cannot be recommended as a preferred method for measuring ventricular volumes and ejection fraction if alternative modalities are readily available.…”
Section: Ventricular Functionmentioning
confidence: 95%
“…Patients with contraindication to CMR (non-compatible pacemakers, defibrillators, or other metal devices) may more easily undergo dedicated CCT studies. CCT is a fast and 24/7 service usually available in emergency context (118), or in clinical daily routine, including the evaluation of coronary arteries and left ventricular function (119).…”
Section: A B and The Assessment Of MI Ischemia And Viability (88)mentioning
confidence: 99%
“…In 2008 Cury et al [11] validated CT first-pass perfusion imaging under resting conditions combined with wall motion and left ventricular function with SPECT serving as gold standard. Blankstein et al [12] validated CT perfusion imaging under adenosine stress against myocardial SPECT and conventional invasive angiography and found a sensitivity of 79% and specificity of 80% for detection of stenosis >50% by CT perfusion alone on a pervessel-basis.…”
mentioning
confidence: 99%
“…Blankstein et al [12] validated CT perfusion imaging under adenosine stress against myocardial SPECT and conventional invasive angiography and found a sensitivity of 79% and specificity of 80% for detection of stenosis >50% by CT perfusion alone on a pervessel-basis. But, radiation dose matters, and radiation dose using 64-slice CT was high with 13.7±3.4 mSv for single [11] and 9.1±3.9 mSv for dual source CT [12], hence the justification of a second delayed enhancement CT dataacquisition became questionable. Moreover, image noise by CT is significantly higher than CMR [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation